2011
DOI: 10.1021/jm2000932
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Half-Sandwich Iridium Anticancer Complexes

Abstract: Abstract:The low-spin 5d 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
340
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 319 publications
(365 citation statements)
references
References 103 publications
19
340
0
3
Order By: Relevance
“…On the other hand, the formation of the mixed hydroxido complexes [RhCp*(L)(OH)] + is completely suppressed in the presence of 0.2 M chloride ions. pK a value of the en complex is found to be higher than that of the bpy under both studied conditions as it was also found for the analogous IrCp* complexes of these ligands [57]. (Fig.…”
Section: Figsupporting
confidence: 79%
See 2 more Smart Citations
“…On the other hand, the formation of the mixed hydroxido complexes [RhCp*(L)(OH)] + is completely suppressed in the presence of 0.2 M chloride ions. pK a value of the en complex is found to be higher than that of the bpy under both studied conditions as it was also found for the analogous IrCp* complexes of these ligands [57]. (Fig.…”
Section: Figsupporting
confidence: 79%
“…However, no comparable H 2 O/Cl -exchange constants for RhCp* complexes are published in the literature to the best of our knowledge, similar findings were found for IrCp* complexes of bpy, en and phen [57], and for some Os and Ru arene complexes as well [49,58]. Fig.…”
Section: Figsupporting
confidence: 75%
See 1 more Smart Citation
“…21 We have previously reported that complex 1 undergoes rapid hydrolysis. 5 based on 1 H NMR peak integrals are shown in Table 2. Figure S2 (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…5 Here we focus attention on the role of the XY chelating ligand in (concentrations at which 50% of the cell growth is inhibited) all > 100 μM. 5 Also Cp* PTA iridium(III) complexes (PTA = 1, 3,5-triaza-7-phosphatricyclo-[3.3.1.1]decane), 7 and Cp* pyTz iridium(III) complexes (pyTz = 2-(pyridine-2-yl)thiazole), 8 are reported to be inactive against A2780 cells (IC 50 values > 300 μM). Sheldrick et al have shown that activity can be switched on by incorporating a DNA intercalator (N,N-chelating polypyridyl ligand) into some Cp* Ir III complexes.…”
Section: Introductionmentioning
confidence: 99%